State-to-state chemical kinetic mechanism for HF chemical lasers. Issue 1 (2nd January 2020) - Li, Hui; Zhao, Tianliang; Li, Jiaxu; Jia, Shuqin; Yang, Dongzheng; Huai, Ying; Sun, Zhigang; Xie, Daiqian; Duo, Liping; Jin, Yuqi
Abstract : State-to-state rotational relaxation processes play a critical role in predicting rotational nonequilibrium, which can significantly affect total laser power and spectral distribution. In this paper, the state-to-state rotational relaxation rate coefficients for the pumping reaction of F + H2, the rotational energy transfer processes of HF( υ, j  = 0–10) + HF( υ′, j′  = 0–10) and HF( υ, j  = 0–10) + H2 are calculated. Subsequently, a detailed state-to-state chemical kinetic mechanism is constructed including 61 species and 124, 482 elementary reactions for HF chemical lasers. All of these rotational relaxation rate coefficients have been expressed with Arrhenius-like formulas. A comparison of the Boltzmann distribution model with the detailed state-to-state chemical mechanism has been analysed and discussed. These results show that rotational nonequilibrium processes can significantly affect the distribution of ro-vibrational excited HF molecules. The rotational distributions of HF( υ  = 0–2, j ) are far from equilibrium distribution. Conversely, the distributions of HF( υ  = 3, 4, j ) seem to be a Boltzmann distribution. These results indicate that numerical models must include the rotational nonequilibrium processes and numerical models using a Boltzmann distribution for the rotational populations cannot predict performance of real HF chemical lasers.